2012
DOI: 10.1002/pmic.201100318
|View full text |Cite
|
Sign up to set email alerts
|

Revealing phosphoproteins playing role in tobacco pollen activated in vitro

Abstract: The transition between the quiescent mature and the metabolically active germinating pollen grain most probably involves changes in protein phosphorylation status, since phosphorylation has been implicated in the regulation of many cellular processes. Given that, only a minor proportion of cellular proteins are phosphorylated at any one time, and that phosphorylated and nonphosphorylated forms of many proteins can co-exist within a cell, the identification of phosphoproteins requires some prior enrichment from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…However, the fern spore germination happens in the medium, therefore, it is somewhat more complex and affected by various environmental factors, such as light, gravity, calcium, phytohormone, and temperature (6). The protein functional skew in fern spores and pollen grains revealed from this study and recent proteomics studies on germinating pollen from kiwifruit (Actinidia deliciosa) (71,72), Nicotiana tabacum (73), rice (Oryza sativa) (26), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78) and Arabidopsis (79,80) presented new evidence for the differentiation of fern spores and spermatophyte pollen (Fig. 10).…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 63%
See 1 more Smart Citation
“…However, the fern spore germination happens in the medium, therefore, it is somewhat more complex and affected by various environmental factors, such as light, gravity, calcium, phytohormone, and temperature (6). The protein functional skew in fern spores and pollen grains revealed from this study and recent proteomics studies on germinating pollen from kiwifruit (Actinidia deliciosa) (71,72), Nicotiana tabacum (73), rice (Oryza sativa) (26), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78) and Arabidopsis (79,80) presented new evidence for the differentiation of fern spores and spermatophyte pollen (Fig. 10).…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 63%
“…No photosynthetic proteins were found in pollen. This highlights that the remodeling of pollen tube cell wall, the loosening and hydrolyzing stigma surface cell and transmitting track of pistil, The data of germinating pollen were summarized and reclassified based on pollen proteomic studies on Oryza sativa (26), Actinidia deliciosa (71,72), Nicotiana tabacum (73), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78), and Arabidopsis thaliana (79,80). The y axis represents the reclassified functional categories, and the x axis shows the percentage of identified proteins.…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 99%
“…These 432 unique phosphorylation sites have been assigned to 301 individual proteins. The number of phosphorylation sites identified represents a great improvement in comparison to our previous tobacco male gametophyte phosphoproteomic study that identified 52 unambiguous phosphorylation sites (21). In that study we applied Al(OH) 3 -metal oxide/hydroxide affinity chromatography for phosphoprotein enrichment (allowing the annotation of only one phosphorylation site), and TiO 2 phosphopeptide enrichment for the analysis of phosphorylation sites of selected candidate proteins from mature pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Seven synthetic peptides were spiked to the peptide mixture in order to check the reproducibility of the replicates. The phosphopeptides bound to TiO 2 beads were washed and eluted as described previously (21,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation